Faith, Illusion and the Church: A Theological Evaluation of Selected Churches in Delta Central Senatorial District - Jemegbe, Mary; Enuwosa, Joseph (NIU Journal of Humanities, 2023)
The study examines faith, illusion and the church: a theological evaluation in the context of selected churches in Delta Central Senatorial District. Religion has been termed illusion because it is used to becloud the mind and make them to believe what does not really exist. If it is an illusion, then any scripture penned by a human is just an illusion. The question is that, how does one engage persons who base their arguments on the claim that religion is just an illusion? The study examines the concept of illusion, faith and the church and brings to bare the inconsequential argument on religion as mere illusion. The study adopted sociological, phenomenological and hermeneutical interpretation of the phenomenon within the context of the Pentecostals with the aim of establishing the correlation between faith and illusion in the context of the church. The conceptual framework of this study is based on the Africentric understanding of the phenomenon of faith from the teachings of Archbishop Benson Andrew Idahosa (1938-1998), who believed the literal text of Heb. 11:1 “Now faith is the substance of things hope for, evidence of things not seen” from a practical dimension. The study argues that faith is the basis of clear thinking therefore, every man has the choice to make; longing for an encounter is the basis for religion. The study concludes that Pentecostal Faith has been criticized and commonly considered as a mixed grill of faith and occult practice, yet there are many things here worshipers who have turned from criticism that people may put forward as a front against Pentecostal exercise of faith and practice. That the Bible is explicit in its teachings when it established that without faith it is impossible to please God, all who live without failure for around the Pentecostal churches should not live to complain rather they should seek to address their background and examine that level of commitment as to the teaching or begin nomination as the basis for a fledgling Christian life and finally that the Apostles of faith from the scriptures and those living examples among us, were all evidence of faith with testimonies and miracles to their record. Keywords: Illusion, Faith, Church and Theology.